Attitude toward seeking school counseling help among Chinese High School students: The role of public stigma and self-stigma: A replication study - Ze, Pan (Animo Repository, 2015)
Public stigma and self-stigma have been implicated as factors in the underutilization of counseling. However, Chinese school counseling services are also underutilized, and yet Chinese scholars know very little about the role of different types of stigma on attitude toward seeking school counseling help among Chinese high school students. Therefore, this study replicated Vogel and colleagues study in 2007 by examining the relationship between public stigma of mental health services and self-stigma of seeking help and attitude toward seeking school counseling help among a sample of 340 Chinese high school students. Results of Multiple Regression analyses indicated that public stigma of mental health services is partially internalized as self-stigma of seeking help and is negatively related to attitude toward seeking school counseling help. In conclusion, self-stigma of seek help is partially mediated public stigma of mental health services on attitude toward seeking school counseling help among Chinese high school students.